Did Marx Have a Labour Theory of Value?. (1st April 2019) - Cockshott, Paul
Abstract : It has long been accepted that Marx was a follower of the labour theory of value. This position has recently been challenged by Harvey. This paper shows that the essential basis of Marx's value theory remained labour and that it did not differ substantially from that of Ricardo. It also references data showing the empirical validity of the theory and presents example data from the UK 1998 input output table showing how closely monetary output shadows labour content.